The Role of Campus Support, Undocumented Identity, and Deferred Action for Childhood Arrivals on Civic Engagement for Latinx Undocumented Undergraduates. Issue 3 (30th August 2017) - Katsiaficas, Dalal; Volpe, Vanessa; Raza, Syeda S.; Garcia, Yuliana
Abstract : This study examined civic engagement in a sample of 790 undocumented Latinx undergraduates (aged 18–30). The relations between social supports (campus safe spaces and peer support) and civic engagement and whether a strong sense of undocumented identity mediated this relation were examined. Competing statistical models examined the role of participants' status (whether or not they received temporary protection from deportation with Deferred Action for Childhood Arrivals [DACA]) in this mediational process. Results revealed that having a strong identification with being undocumented mediated the role of social supports on civic engagement in the overall sample, and that this process was specifically important for those with DACA status. The intersection of policies such as DACA and the lived experiences of Latinx undocumented college students are discussed.